Economics of livestock-based farming systems in saline and normal areas of West Bengal: A comparative analysis - Das, Arghyadeep; RAJU, R.; R. MALHOTRA; AJMER SINGH; SANJIT MAITI; RAKESH KUMAR; NEELA MADHAV PATNAIK (Indian Journal of Dairy Science, 2024)
Salinity has deleterious effects on both crops and livestock. The present study evaluated the impact of salinity and estimated the cost and return of different livestock-based farming systems in saline and normal areas of West Bengal. The study suggested the farmers the best farming system to be adopted based on output-input ratio. Saline areas are dominated by the indigenous cow and normal areas by the crossbreed jerseys. This was due to a shortage of green fodder in saline areas. Cattle+goat+crop (N2) had highest crop area (1.80 acres) while Cattle+goat+crop+fish (S3) had highest fishing area (0.70 acres). Due to low maintenance cost, Sheep+poultry (S1) and Goat+poultry (S2) farming systems had output-input ratios close to 2. Whereas other farming systems in saline areas, the output-input ratios were close to 1.5. In case of normal areas, Cattle+goat+crop+fish had the highest output-input ratio of 1.58. Goat+poultry (S2) farming system had the highest net return of ₹53,967.68 per annum among landless farmers and cattle+goat+crop+fish (S3) with a net return of ₹1,01,686.50 per annum among landholders in saline areas. The farming system, Cattle+goat+poultry+crop (N1) had highest net return of ₹1,15,578 per annum) in normal areas. Share of labour was highest (56% to 58%) in total cost in crop enterprises and feed and fodder cost had a major share (53% to 72%) in total cost for livestock enterprises. Share of cattle enterprise in total cost and net return was highest. However, its share in net return was lower than its share in total cost. In case of goat and fish enterprises, their share in net return was higher than their share in total cost.